2016
DOI: 10.1016/j.jadohealth.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Neighborhood Food Store Environment and Children's Body Mass Index at Peripuberty in the United States

Abstract: Background Little is known about the relationship between changes in food store environment and children’s obesity risk in the US. This study examines children’s weight status associated with the changes in the quantity of food stores in their neighborhoods. Methods A nationally representative cohort of schoolchildren in the US was followed from 5th grade in 2004 to 8th grade in 2007 (n=7090). In 2004 and 2007, children’s body mass index (BMI) was directly measured in schools. ZIP-Code Business Patterns data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 37 publications
5
52
1
2
Order By: Relevance
“…Present analyses also did not examine how neighborhood environment may be impacting children’s within-home environments or how much exposure children or their parent(s)/caregiver(s) had to their neighborhood environment, although prior analyses from this study did find relationships between parenting practices/rules around eating and children’s diet quality [37]. Unlike Chen and colleagues [12], this study did not examine changes to environments over time. More natural experiments are needed to evaluate changes in policies, systems, and environments designed to, or that may inadvertently, affect children’s weight outcomes [38].…”
Section: Discussionmentioning
confidence: 89%
“…Present analyses also did not examine how neighborhood environment may be impacting children’s within-home environments or how much exposure children or their parent(s)/caregiver(s) had to their neighborhood environment, although prior analyses from this study did find relationships between parenting practices/rules around eating and children’s diet quality [37]. Unlike Chen and colleagues [12], this study did not examine changes to environments over time. More natural experiments are needed to evaluate changes in policies, systems, and environments designed to, or that may inadvertently, affect children’s weight outcomes [38].…”
Section: Discussionmentioning
confidence: 89%
“…There are stark differences in local food environments in the US according to the community’s racial and economic composition (Franco et al 2008; Kumanyika et al 2014; Raja, Ma, and Yadav 2008), and these differences are thought to be related to obesity (Walker, Keane, and Burke 2010; Odoms-Young, Zenk, and Mason 2009; Gordon-Larsen 2014). In two recent studies, the retail food environment was found to be associated with childhood obesity; with supermarkets being protective, and small stores enhancing risk (Chen and Wang, 2016; Tang et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Morland and colleagues reported that the presence of convenience stores was associated with higher obesity prevalence [62]. Despite the studies yielding statistically significant results in the desired direction [51, 54, 56, 62, 6568], a fair percentage of studies observed null findings [52, 55, 57, 58, 6971]. Contrary to most findings, studies reporting unexpected or negative results also exist in the literature [49, 50, 55, 57].…”
Section: Food Retail Environment and Obesity Riskmentioning
confidence: 99%
“…The vast majority of the studies conducted have employed a cross-sectional study design [12••, 49, 51, 54, 56, 62, 6569]. Longitudinal studies in this area have been limited [50, 52, 58, 63, 71]. Thus, the lack of experimental studies and longitudinal analyses make it difficult to assess underlying relationships between the food environment and obesity.…”
Section: Food Retail Environment and Obesity Riskmentioning
confidence: 99%